“Hope I’ll have hope” – industrial decline, insecurity and transition in Croatian province - Potkonjak, Sanja; Škokić, Tea (2012)
The paper explores life stories of women workers who have spent their lives working in hard industry. By problematizing transition and looking at women working force this paper aims at questioning the ongoing imaginary of alternative economies, the meaning of hope and despair.
Projekt MZOS
Projekt MZOS
ENG